If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (u + -3)(u + 4) = 0 Reorder the terms: (-3 + u)(u + 4) = 0 Reorder the terms: (-3 + u)(4 + u) = 0 Multiply (-3 + u) * (4 + u) (-3(4 + u) + u(4 + u)) = 0 ((4 * -3 + u * -3) + u(4 + u)) = 0 ((-12 + -3u) + u(4 + u)) = 0 (-12 + -3u + (4 * u + u * u)) = 0 (-12 + -3u + (4u + u2)) = 0 Combine like terms: -3u + 4u = 1u (-12 + 1u + u2) = 0 Solving -12 + 1u + u2 = 0 Solving for variable 'u'. Factor a trinomial. (-4 + -1u)(3 + -1u) = 0Subproblem 1
Set the factor '(-4 + -1u)' equal to zero and attempt to solve: Simplifying -4 + -1u = 0 Solving -4 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1u = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1u = 0 + 4 -1u = 0 + 4 Combine like terms: 0 + 4 = 4 -1u = 4 Divide each side by '-1'. u = -4 Simplifying u = -4Subproblem 2
Set the factor '(3 + -1u)' equal to zero and attempt to solve: Simplifying 3 + -1u = 0 Solving 3 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1u = 0 + -3 -1u = 0 + -3 Combine like terms: 0 + -3 = -3 -1u = -3 Divide each side by '-1'. u = 3 Simplifying u = 3Solution
u = {-4, 3}
| -3x^2-24x+12=10 | | (2y-7)=(14-2)+4y | | ((5^(-1/2))*(5x^(5/2)))/(5x)^(3/2) | | y=-5/7x | | 1/10x^3-15/2-25 | | 8-2(4-1)= | | x^2-2xy+y^2-6x-6y-1=0 | | 8x+4(-2x-1)=-4 | | x^2+2xy+y^2-6x-6y-1=0 | | 1/2x-5/6=2x-3/4 | | 64.5x/6-3x/4=x-11 | | q-p=6 | | 2x-4=5+6x | | (Y)=7 | | 9p+3q=-2 | | 3z+6(z+3)-10= | | 4y+4y=-16 | | F(4z)=3x^2+4 | | X+2X+2=4 | | h=1.5+8.4t+-4.9t^2 | | 6y-3(y+4)+3(y-6)= | | 4*3/10 | | 3(4a-8)+12= | | 8x+4(-2X+1)=-4 | | 22=8X-3 | | -(3/2)X=4/7 | | 16x+11x+16y-20y+6-10= | | 24=18-2q | | 24=18-29 | | x=1.2+0.6x | | -38=3(y-6)-5y | | 4x-3/2=-3/2x-6/5 |